Effect Evaluation of Mental Nursing in Nursing of Young Cancer Patients Based on Big Data - Ren, Yuanpeng (Frontiers in Public Health, 2022)
The field of mental health nursing has always been special, dynamic, and flexible in terms of enhancing individuals' quality of life. Mental health nursing is all about caring for individuals with mental health disorders with the aim of helping them recover from illness, thereby improving their living conditions. Health Education of mental nursing emphasizes on providing special care to patients and optimally fulfills the clinical outcomes of the patients. It has been widely accepted that mental illness negatively influences the well-being of individuals, irrespective of their age, origin, demography, social status, and economic status. Young patients diagnosed with cancer report that they have a poor quality of life, as they undergo several physical and psychological needs, especially after the surgery and other cancer-related treatments. Thus, this study aims to examine the effect of mental health nursing on nursing young patients with cancer, based on the big data. Thus, the study conducts longitudinal analysis of the data gathered from the young patients with cancer, monitored by mental health nurse, with advanced practice nurse (APN) interventions. Results of the study stated that APN interventions positively impacted the physical as well as psychological needs of the research subjects. Mental nursing interventions resulted in positive clinical outcomes of the patients.